Implementation of a neighbourhood care model in a Scottish integrated context-views from patients - Calum F Leask; Andrea Gilmartin (AIMS Press, 2019)
There is a need to test new models of integrated health and social care, particularly due to increasing financial and epidemiological pressures on services. One critical component of testing new models is the acceptability to patients. Here, the aim was to understand the acceptability of a new model of care to patients by understanding their experience of being supported by a self-managing, community-based, integrated, health and social care team. The INCA service consisted of three support workers and three nurses in two teams. These teams were self-managing and had autonomy over service operations and care delivery. Eight interviews and satisfaction questionnaires were conducted with patients. Interviews were transcribed and analysed thematically. Patients found the service highly acceptable (mean overall satisfaction of 98%), self-reporting a variety of benefits to their wellbeing. Central to this acceptability was the autonomy of staff to adjust care frequency and duration to patients' needs, in addition to describing an active engagement and partnership within their support plans. Future work should aim to ascertain the experiences of staff working in this model and whether receiving support in this way improves clinical outcomes.